Strategi Perencanaan Sumber Daya Manusia (SDM) Dengan Metode Analisis SWOT Di Bank BUMN X (Salah satu Bank BUMN Terbesar Di Indonesia) - Rizki Anugrah Wibowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to find out how the human resource planning strategy is carried out by one of the state-owned banks (BUMN). This BUMN bank is one of the largest banks in Indonesia and has good credibility in Indonesia. So in this study analyzed whether existing human resources are effective or not. The type of research conducted is Field Research which is descriptive in nature, namely research that describes human resource planning strategies in an effort to improve employee performance. Data collected by means of interviews, observation, and documentation. The data analysis technique used is descriptive qualitative analysis combined with the SWOT analysis approach. The results of the research explain that in human resource planning there are several stages in the process of procuring new employees. And during the course of its business activities, the company sees the strengths, weaknesses, opportunities and threats that at one time can be profitable or vice versa will be detrimental to the company. Keywords: Human Resource Planning; SWOT analysis